The effects of a commercially available warm-up program on landing mechanics in female youth soccer players - Grandstrand, S. L.; Pfeiffer, R. P.; Sabick, M. B.; DeBeliso, M.; Shea, K. G. (The Journal of Strength and Conditioning Research, 2006)
The purpose of this study was to examine lower extremity kinematics following implementation of the Sportsmetrics Warm-Up for Injury Prevention and Performance (WIPP) training program. The hypothesis was that there would be no difference in landing mechanics between 2 groups of female youth soccer players (9-11 years of age), with 1 group (Treatment) completing the 8-week- duration (2 days per week) WIPP program and the other serving as a Control group. We recruited 21 female youth soccer players. Treatment (n = 12) and Control (n = 9) groups were established. Using the Sportsmetrics Software for Analysis of Jumping Mechanics, we analyzed lower extremity movement during landing after subjects jumped off a 30.5-cm box and immediately went into a vertical jump. No significant changes in knee separation values were observed in the Treatment group after 8 weeks of WIPP training. The results indicate that 8 weeks of WIPP training did not significantly alter landing strategies.